Emerging Aeromonas spp. infections in Europe: characterization of human clinical isolates from German patients - Schwartz, Keike; Borowiak, Maria; Strauch, Eckhard; Deneke, Carlus; Richter, Martin H.; , The German Aeromonas Study Group (Frontiers in Microbiology, 2024)
Bacteria of the genus Aeromonas are widely distributed in water bodies around the world. Some Aeromonas species have been identified as human pathogens causing intestinal and a variety of extraintestinal infections. In Germany, information on diseases caused by Aeromonas is rare, because Aeromonas infections are not notifiable in Germany. To address this information gap and gain better insights, a successful collaboration with human medical diagnostic laboratories within Germany was established and several Aeromonas isolates from diseased patients were sent to the Aeromonas laboratory of the German Federal Institute for Risk Assessment. 52 clinical Aeromonas isolates, of which anonymized patients’ data were available, were selected for further characterization by MALDI-TOF MS, biochemical testing, and whole genome sequencing (WGS). Nearly half of the isolates were from patients older than 60 years, whereas only four isolates were from patients aged up to 10 years. 30 isolates originated from stools of patients with diarrhea/(gastro-)enteritis and 22 strains were from patients with diverse extraintestinal infections, such as wound infection, septicemia, bursitis, abscesses, cholangitis, urinary tract infections, and pneumonia. Taxonomical identification revealed following predominant species: A. veronii biovar sobria (18 isolates), A. caviae (17 isolates), and A. hydrophila (nine isolates). Two A. salmonicida isolates and one isolate each of A. dhakensis, A. bestiarum, and A. encheleia were also identified. Three closely related intestinal isolates could not be assigned to a recognized Aeromonas species. The clustering of strains based on virulence factor profile resulted in a grouping that closely resembles the clustering of the phylogenetic tree suggesting that the profiles are specific for each species. Our study on clinical Aeromonas isolates characterizes for the first time human pathogenic strains isolated in Germany. These bacteria are important microorganisms within the One Health context because of their ubiquitous presence in the environment and as a cause of opportunistic infections in humans and animals. Infections caused by Aeromonas bacteria show a seasonality with increased infection rates in warmer periods. In view of climate change, Aeromonas bacteria are regarded as emerging pathogens and research is required to determine the reservoirs in One Health sources from which human infections may arise.